Proline Metabolism is Essential for Trypanosoma brucei brucei Survival in the Tsetse Vector. - Brian S Mantilla; Letícia Marchese; Aitor Casas-Sánchez; Naomi A Dyer; Nicholas Ejeh; Marc Biran; Frédéric Bringaud; Michael J Lehane; Alvaro Acosta-Serrano; Ariel M Silber (PLoS Pathogens, 2017)
Adaptation to different nutritional environments is essential for life cycle completion by all Trypanosoma brucei sub-species. In the tsetse fly vector, L-proline is among the most abundant amino acids and is mainly used by the fly for lactation and to fuel flight muscle. The procyclic (insect) stage of T. b. brucei uses L-proline as its main carbon source, relying on an efficient catabolic pathway to convert it to glutamate, and then to succinate, acetate and alanine as the main secreted end products. Here we investigated the essentiality of an undisrupted proline catabolic pathway in T. b. brucei by studying mitochondrial Δ1-pyrroline-5-carboxylate dehydrogenase (TbP5CDH), which catalyzes the irreversible conversion of gamma-glutamate semialdehyde (γGS) into L-glutamate and NADH. In addition, we provided evidence for the absence of a functional proline biosynthetic pathway. TbP5CDH expression is developmentally regulated in the insect stages of the parasite, but absent in bloodstream forms grown in vitro. RNAi down-regulation of TbP5CDH severely affected the growth of procyclic trypanosomes in vitro in the absence of glucose, and altered the metabolic flux when proline was the sole carbon source. Furthermore, TbP5CDH knocked-down cells exhibited alterations in the mitochondrial inner membrane potential (ΔΨm), respiratory control ratio and ATP production. Also, changes in the proline-glutamate oxidative capacity slightly affected the surface expression of the major surface glycoprotein EP-procyclin. In the tsetse, TbP5CDH knocked-down cells were impaired and thus unable to colonize the fly's midgut, probably due to the lack of glucose between bloodmeals. Altogether, our data show that the regulated expression of the proline metabolism pathway in T. b. brucei allows this parasite to adapt to the nutritional environment of the tsetse midgut.